A Olimpíada Nacional em História do Brasil: o ensino de história para além da sala de aula - NASCIMENTO, Márcio dos Santos do (Universidade Federal do Pará, 2025)
This study investigates History Education as a process of knowledge production through the participation of students in the Brazilian National History Olympiad (ONHB). It seeks to understand whether research develops skills not only in the classroom but also in other learning spaces. Created in 2009 by Unicamp, the ONHB aims to encourage the study and research of Brazilian History, promoting integration among schools, teachers, and students. The research was conducted in two private schools in Belém, Pará, involving both participants and non-participants of the ONHB. Discursive questionnaires were used to investigate students' perceptions of History Education and the influence of the competition on their development. The analysis focused on identifying how the use of historical sources and documents stimulates critical debates and varied thematic approaches, promoting reflective argumentation and students' protagonism both in the classroom and in the competition. Additionally, it sought to understand how non-participating students perceive the value of historical knowledge and the impact of the ONHB on their peers' development. The problematization arises from the perspective of behavioral changes among ONHB participants, questioning whether classroom History lessons limit students' critical capacity. Other inquiries include: the gap between History Education in Basic Education and academic research; whether History classes are outdated, overly content-driven, or less engaging; and what role teachers play in fostering student protagonism. The results indicate that the ONHB plays a fundamental role in transforming History Education in Brazil, broadening historical interpretations, developing critical thinking, and fostering research skills in students. The competition stands out by encouraging investigation and critical reflection on the past and present. In summary, the ONHB promotes participatory and meaningful education.